THREE POINTS OF FOCUS IN ENHANCING UNIVERSITYINDUSTRY NETWORKING - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 30 March 2015 – The 4th ASEM Rectors’ Conference in Hangzhou, China which was attended by nearly 100 representatives from universities in Asia and Europe recently sought to address how universities could cooperate with the business sector to equip the university community with employability skills, foster entrepreneurship and create new learning environments.